2019
DOI: 10.3389/fimmu.2019.02474
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Parameter Analysis of Biobanked Human Bone Marrow Stromal Cells Shows Little Influence for Donor Age and Mild Comorbidities on Phenotypic and Functional Properties

Abstract: Heterogeneous populations of human bone marrow-derived stromal cells (BMSC) are among the most frequently tested cellular therapeutics for treating degenerative and immune disorders, which occur predominantly in the aging population. Currently, it is unclear whether advanced donor age and commonly associated comorbidities affect the properties of ex vivo-expanded BMSCs. Thus, we stratified cells from adult and elderly donors from our biobank (n = 10 and n = 13, mean age 38 and 72 years, respectively) and compa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(96 citation statements)
references
References 102 publications
7
89
0
Order By: Relevance
“…While the sample size of the study was not large enough to assess the nature of these differences, the analysis showed that the interlaboratory differences made a greater contribution to MSC variability than did differences among BM donors. This aligns with a recent study reporting that variable in vitro expansion strategies (i.e., passaging or "in vitro aging") have a stronger impact on MSC molecular phenotype than donor age (Andrzejewska et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…While the sample size of the study was not large enough to assess the nature of these differences, the analysis showed that the interlaboratory differences made a greater contribution to MSC variability than did differences among BM donors. This aligns with a recent study reporting that variable in vitro expansion strategies (i.e., passaging or "in vitro aging") have a stronger impact on MSC molecular phenotype than donor age (Andrzejewska et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…While the quantitative distribution of PRAT-SVF endothelial cells was comparable in ECD and non-ECD donors, we observed a high inter-individual variability in PRAT-SVF angiogenic activity, that did not reach significance between the ECD and non-ECD groups analyzed in the present study. Such heterogeneity among donors has already been reported for mesenchymal stem cells (26). However, in line with this result, the study by Aird et al did not evidence major changes in the angiogenic potential of AT-SVF with aging except a delayed phase of neovessels maturation in vivo (46).…”
Section: Discussionsupporting
confidence: 76%
“…We and others have reported that the phenotypic and angiogenic activity of ECFC can be altered in deceased contexts associated with cardiovascular risk factors or genetic or epigenetic determinants (23)(24)(25). Furthermore, it was recently demonstrated that donor age and comorbidities can alter the angiogenic and paracrine immunosuppressive properties of human bone marrow-derived stromal cells (BM-SC) obtained after in vitro cell culture expansion (26). It is thus likely that the ECD microenvironment can also alter the vascular potential of the various types of PRAT SVF-resident cells.…”
Section: Introductionmentioning
confidence: 99%
“…MSC isolation and characterization was performed as described previously. [72] OBs were isolated from diced cancellous bone and characterized as described previously by others. [73] The cell culture medium for MSCs and OBs was Dulbecco's modified Eagle's medium with 10% fetal calf serum, 5 mm l-alanyl-lglutamine and 100 U mL −1 penicillin plus 100 µg mL −1 streptomycin.…”
Section: Nano-x-ray Fluorescence Mappingmentioning
confidence: 99%